School outcomes in children registered in the Studies for Pediatric Liver Transplant (SPLIT) consortium - Gilmour, Susan G (2010)
School performance is an important aspect of functional outcomes for pediatric liver transplant (LT) recipients. This longitudinal analysis conducted through the Studies of Pediatric Liver Transplantation (SPLIT) research consortium examines several indicators of school function in these patients. Thirty-nine centers participated in data collection using a semi-structured questionnaire designed specifically for this study. The survey queried school attendance, performance and educational outcomes including the need for special educational services. Participants included 823/1133 (73%) of eligible patients, mean age 11.34±3.84, 53% female, median age at LT 4.6 (range 0.05-17.8) years, and mean interval from transplant was 5.42±2.79. Overall, 34% of patients were receiving special educational services and 20% had repeated a grade, with older participants more likely to have been held back (p=0.0007). Missing more than 10 days of school per year was reported by one third of the group with this level of absence being more common in older participants (p=0.0024) and children with shorter intervals from LT (<0.0001). Multivariate analysis revealed the following factors were associated with the need for special educational services; type of immunosuppression at six months post-LT, CSA (OR 1.8, CI:1.1-3.1), or other (OR 4.9, CI:1.4-17.6) versus tacrolimus, symptomatic CMV infection within 6 months of LT (OR 3.1:CI 1.6-6.1), and pre-transplant special educational services (OR 22.5, CI:8.6-58.4).